Sharing Knowledge of Roles in Mediating The Influence of Organizational Culture, Organizational Climate on Productive Behavior at Hospital - Rahma Fajriati; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of competence, leadership style, and work discipline on employee motivation at PT. Mapan Putra Sentosa Sidoarjo. The population used in this study are employees of PT. Mapan Putra Sentosa Sidoarjo, totaling 55 people. By using the sampling technique Quota Sampling, where in this technique the emphasis is on taking samples based on the total population. This research was conducted with quantitative methods. The data collection technique used is a questionnaire. The data analysis technique used in this research is multiple linear regression using SPSS version 22 for windows. The results of this study indicate that, Competence does not have a partially significant effect on employee work motivation, leadership style has a partially significant effect on employee work motivation, work discipline has a partially significant effect on employee work motivation. Competence, Leadership Style, and Work Discipline have a simultaneous effect on employees' work motivation. Leadership style is the most significant variable on employee motivation.